Caratteristiche del trattamento comunitario: fattori aspecifici della cura - Sneider, Giovanni (Il sogno della farfalla, 2018)
The article describes the unspecific therapeutic aspects of communities, meaning the aspects that lead a severe patient to enter a group psychotherapy setting, that is, a specific treatment milieu. Amongst the many different unspecific factors that contribute to the success of the therapy, the author analyzes two in particular: the atmosphere within the community and familiarity. The atmosphere of communities is determined by individuals’ features and the relationships between the people who work there, which makes it possible for patients to partake in the therapeutic process despite their crisis. Familiarity is the way the people who work there stay with patients which determines a first moment of being together with others.